Pengaruh Kualitas Layanan Terhadap Loyalitas Pelanggan Di Tengah Persaingan Jasa Laundry (Studi Pada Aida Laundry Jember) - Jumaidah; Hanif Hadinata Utama; Hermawan Teguh Saputra (LPPM Universitas Bina Sarana Informatika Kampus Kabupaten Banyumas, 2026)
This study was conducted to examine how service quality affects customer loyalty at Aida Laundry in Jember Regency. To maintain customer retention amid fierce competition in the laundry business, improving service quality is a strategy that must be implemented by business operators. This study applied a quantitative method designed in the form of explanatory research. The sample in this study involved 50 respondents selected through accidental sampling. Research data was obtained through the distribution of a five-point Likert scale questionnaire, then analyzed using descriptive statistics and simple linear regression methods. Based on the analysis results, service quality was proven to have a positive and significant effect on customer loyalty, as indicated by a significance value of 0.021, which is less than 0.05. The coefficient of determination value of 10.6% indicates that variations in customer loyalty can be explained by service quality, while the rest is influenced by other variables that were not studied. The results of this study reinforce that customer loyalty can be built through improving service quality, which includes the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. Thus, Aida Laundry is encouraged to continuously improve its service quality in order to maintain customer loyalty and strengthen its business competitiveness